2020
DOI: 10.5271/sjweh.3907
|View full text |Cite
|
Sign up to set email alerts
|

Office design as a risk factor for disability retirement: A prospective registry study of Norwegian employees

Abstract: Office design as a risk factor for disability retirement: A prospective registry study of Norwegian employees by Nielsen MB, Emberland JS, Knardahl S Little is known about the impact of office design on the work ability of employees. Using official registry data on disability retirement, this study shows that employees working in shared offices and open-plan workspaces have a significantly higher risk of disability retirement compared to employees working in cellular offices even after adjusting for demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The finding that moving from shared and open office designs to cellular offices is likely to increase the perceptions of control extends previous cross‐sectional research on office design and job control (Van Hootegem & De Witte, 2017) and is in line with longitudinal studies reporting more negative working conditions and more health problems among employees in shared and open workspaces (Bergstrom, Miller & Horneij, 2015; Brennan, Chugh & Kline, 2002; Nielsen, Emberland & Knardahl, 2020). Allowing workers to decide their own working hours, choose their work location, and organize their tasks autonomously are important for enhancing the experience of control (Bailey & Kurland, 2002; Mann et al ., 2000).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The finding that moving from shared and open office designs to cellular offices is likely to increase the perceptions of control extends previous cross‐sectional research on office design and job control (Van Hootegem & De Witte, 2017) and is in line with longitudinal studies reporting more negative working conditions and more health problems among employees in shared and open workspaces (Bergstrom, Miller & Horneij, 2015; Brennan, Chugh & Kline, 2002; Nielsen, Emberland & Knardahl, 2020). Allowing workers to decide their own working hours, choose their work location, and organize their tasks autonomously are important for enhancing the experience of control (Bailey & Kurland, 2002; Mann et al ., 2000).…”
Section: Discussionsupporting
confidence: 85%
“…Taking into consideration that past research has identified control as a main antecedent to work ability (Knardahl et al, 2017;Knardahl, Sterud, Nielsen & Nordby, 2016), our findings indicate that lower levels of control over work intensity may be one potential explanatory mechanism in the previously established relationship between office design and health outcome such as sickness absence/disability retirement (Nielsen, Emberland & Knardahl, 2020;Nielsen & Knardahl, 2019). As job demands are associated with job strain, exhaustion, and mental distress (Bakker & de Vries, 2021;Stansfeld & Candy, 2006), providing employees with an experience of control of work intensity could therefore be important with regard to sustaining health, wellbeing, and productivity when moving to an open-plan office workplace.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Rather, contextual factors need to be taken into account, such as climate and personal attitudes. A recent Norwegian study reported effects of personality, such as gender and health status, including that open and shared workspace designs increase the risk of disability retirement among office workers [46].…”
Section: Plos Onementioning
confidence: 99%
“…While office work is changing along several dimensions, such as office design (eg, private versus open-plan offices), office use (eg, fixed versus shared seating), and office location (eg, at work versus at home) ( 1 ), most research have been limited to studying office design in isolation ( 4 ). Synthesized evidence from this research stream suggests differences in experiences of health and well-being across office designs ( 2 , 4 ) and unfavorable health outcomes – such as increased risk of sickness absence ( 8 ) and disability retirement ( 9 ) – for employees in shared -room and open-plan offices. Yet, these observed differences are likely not a product of office design alone but contingent on other aspects of contemporary office work.…”
mentioning
confidence: 99%